ANALISIS KETIMPANGAN PENDAPATAN DI PROVINSI ACEH - Meliza Meliza; Murtala Murtala (LPPM UNIMAL, 2020)
Thisstudyaimsto analyze the factorsthatinfluence income inequality in Aceh Province. This study uses secondary data obtained from the Central Bureau of Statistics of Aceh Province in 2010-2017. Data analysis techniques used are the williamsonindex, entropytheil index, and multiplelinear regression analysis. Thetestresults using the Williamson index show that income inequality in Aceh Province is still quite high at 0.41%, and from the entropy theil index testing shows very high-income inequality at 1.47%, Economic growth (Growth) does not affect income inequality (INEQ) The unemployment rate (Unemp) does not affect income inequality (INEQ), the Gross enrollment rate (GER) affects income inequality (INEQ), and Agglomeration (Aglo) does not affect income inequality (INEQ).Keywords: income inequality.